Analisis Pengaruh Parameter Konduktivitas, Resistivitas dan TDS Terhadap Salinitas Air Tanah Dangkal pada Kondisi Air Laut Pasang dan Air Laut Surut di Daerah Pesisir Pantai Kota Padang - Khairunnas Khairunnas; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract.The geographical boundary of the Padang city bordering the sea has an impact like the potential for sea water intrusion. Guo and Jiao in Amri (2014) naturally seawater cannot enter far into the land because ground water has piezometric which suppresses more strongly than sea water, so an interface is formed as the boundary between groundwater and sea water. This situation is an equilibrium condition between sea water and ground water. Therefore the potential for sea water to enter land is only around the coast.This research was carried out at 107 measurement points scattered around the coastal area of Padang City. The data obtained are primary data obtained based on measurements in the field, namely data on the value of Salinity, Conductivity, Resistivity and TDS of shallow groundwater in high tide and low tide seawater conditions.Based on the measurement results obtained 7 measurement points which are considered anomalies, which have values that are far different from the overall measurement point. Perform Linear Regression Analysis and Correlation using Microsoft Excel and SPSS. Zoning mapping is obtained from processing data using ArcGis software. Keywords:Salinity, Conduktivity, Resistivity, TDS, Sea Water Intrusion